2015
DOI: 10.1111/tpj.12925
|View full text |Cite
|
Sign up to set email alerts
|

Exploring diterpene metabolism in non‐model species: transcriptome‐enabled discovery and functional characterization of labda‐7,13E‐dienyl diphosphate synthase from Grindelia robusta

Abstract: SUMMARYGrindelia robusta or gumweed, is a medicinal herb of the sunflower family that forms a diverse suite of diterpenoid natural products. Its major constituents, grindelic acid and related grindelane diterpenoids accumulate in a resinous exudate covering the plants' surfaces, most prominently the unopened composite flower. Recent studies demonstrated potential pharmaceutical applications for grindelic acid and its synthetic derivatives. Mining of the previously published transcriptome of G. robusta flower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 48 publications
1
29
0
10
Order By: Relevance
“…This secondary product is likely resulting from thermal degradation of copalol during GC-MS analysis as previously observed in transient expression analyses of other class II diTPSs [21, 24, 37, 46]. In contrast to IrTPS5, sequential activity of IrTPS3 was only detected with MvELS yielding miltiradiene (product e), whereas no product formation was detected after co-expression with GrEKS (Fig 3B).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…This secondary product is likely resulting from thermal degradation of copalol during GC-MS analysis as previously observed in transient expression analyses of other class II diTPSs [21, 24, 37, 46]. In contrast to IrTPS5, sequential activity of IrTPS3 was only detected with MvELS yielding miltiradiene (product e), whereas no product formation was detected after co-expression with GrEKS (Fig 3B).…”
Section: Resultssupporting
confidence: 68%
“…Due to the natural pairwise activity of monofunctional class II and class I diTPSs in angiosperm labdane biosynthesis [16, 20, 34, 35], combinatorial expression of class II and class I diTPSs can be used to determine the identity and stereochemistry of enzyme products [21, 23, 24, 3645]. To this end, we co-expressed IrTPS5 and IrTPS3 with previously characterized class I diTPSs that exhibited substrate-specificity to ent -CPP ( Grindelia robusta ent -kaurene synthase, GrEKS [37]) and (+)-CPP ( Marrubium vulgare epoxy-labdane/miltiradiene synthase, MvELS [21]), respectively. Transient expression of IrTPS5 alone yielded copalol (product a) as verified by comparison to an enzyme-produced standard (Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results not only confirm the function of Fl-SdKPS as KPS, but also indicate that (–)-kolavenyl diphosphate can be dephosphorylated to (–)-kolavenol by an endogenous enzyme from N. benthamiana leaves. It has been previously suggested that endogenous phosphatases can convert the product of class II diTPSs into corresponding diterpenols in tobacco (Sallaud et al , 2012; Zerbe et al , 2014, 2015). Thus, in vivo functional characterization of Fl-SdKPS confirmed the results obtained in vitro with Tr-SdKPS.…”
Section: Resultsmentioning
confidence: 99%